Brazilian guideline for the use of immunobiologicals in chronic rhinosinusitis with nasal polyps ‒ 2024 update - Anselmo-Lima, Wilma T.; Romano, Fabrizio R.; Tamashiro, Edwin; Roithmann, Renato; Dinarte, Vanessa R.P.; Piltcher, Otavio B.; Miyake, Marcel M.; Fornazieri, Marco A.; Nakanishi, Marcio; Bezerra, Thiago F.P.; Dolci, Ricardo L.L.; Mello Jr, João F.; et al. (Elsevier, 2024)
Introduction: Biologics targeting type 2 inflammation have revolutionized the way we treat patients with Chronic Rhinosinusitis with Nasal Polyps (CRSwNP). Particularly in severe and difficult-to-control cases, these drugs have provided a new reality for these patients, allowing for the effective and safe treatment of extensive diseases that were not completely managed with the typical strategy of surgery and topical medications. Objectives: The experience achieved with the approval of these medications by ANVISA for use in CRSwNP and the knowledge obtained regarding outcomes, adverse effects, and the ideal patient profile prompted the update of the previously published guideline, with a detailed review of the most recent scientific literature, the personal experiences of experts, and the adaptation to the reality of the Brazilian healthcare system, both public and private. Results: We proposed a new eligibility criterion for biologics in patients with CRSwNP based on four pillars of indication: the impact of the disease on the patient's life, whether in the presence of specific symptoms or in overall quality of life; the extent of sinonasal disease; the presence of type 2 comorbidities, considering other associated diseases that may also benefit from anti-T2 biologics, and the presence of biomarkers to define type 2 inflammation, especially those associated with worse disease prognoses. Conclusions: This innovative and pioneering method has two major advantages. First, it ensures a comprehensive evaluation of patients; second, it is flexible, as advancements in our understanding of the disease and changes in cost-effectiveness can be addressed by simply adjusting the required score for indication, without the need to modify the entire evaluation scheme.
Keywords: Biologicals; Chronic rhinosinusitis; Monoclonal antibodies; Nasal polyp